Bibliometric analysis of authorship patterns in publications from a research group at the London School of Hygiene & Tropical Medicine, 2016–2020. Issue 2 (15th February 2023) - Shambe, Iornum; Thomas, Katherine; Bradley, John; Marchant, Tanya; Weiss, Helen A; Webb, Emily L
Abstract : Background: Authors from low and middle-income country (LMIC) institutions are under-represented in publications of research based in LMICs. This case study of publications from authors within the Medical Research Council International Statistics and Epidemiology Group (MRC-ISEG), a global health research group affiliated to the London School of Hygiene & Tropical Medicine in the UK, aims to describe patterns in authorship and factors associated with under-representation. Methods: Papers were included if they were published between January 2016 and December 2020 inclusive, included an author from the MRC-ISEG and described work conducted in a LMIC. Authors' affiliations were classified using World Bank country income classifications into LMIC affiliations only, high-income country (HIC) affiliations only and mixed LMIC/HIC affiliations. Multinomial logistic regression analysis was used to assess associations of author affiliation category with authorship position, and whether patterns varied by journal impact factor quartile and multiple versus single-country studies. Results: A total of 882 papers, including 10 570 authors describing research conducted in 61 LMICs, were included. Compared with authors of HIC-only affiliation, those with LMIC-only affiliation were less likely to be in first authorship position (relative risk ratio (RRR)=0.51, 95% CI 0.44 to 0.60) and mixed HIC/LMIC affiliation authors were more likely (RRR=2.80, 95% CI 2.35 to 3.34). Compared with authors of HIC-only affiliation, those with LMIC-only affiliation were less likely to be in last authorship position (RRR=0.20, 95% CI 0.16 to 0.24) and those with mixed HIC/LMIC affiliations were more likely (RRR=1.95, 95% CI 1.65 to 2.30). The proportion of senior authors with LMIC-only affiliation was lowest for the highest impact journals, and in multicountry versus single-country studies. Conclusion: Alongside increasing research capacity within LMICs, HIC institutions should ensure that LMIC-affiliated researchers are properly represented in global research. Academics working in global health should be judged on their involvement in representative collaborative research rather than individual achievements in authorship position.